PENGARUH ELECTROPOLISHING PADA BAJA TAHAN KARAT AISI 316L YANG MENGALAMI DEFORMASI DINGIN TERHADAP KEKASARAN DAN KEKERASAN PERMUKAAN UNTUK MENDUKUNG KEBUTUHAN MEDIS - Ahmadi, Nurfi (SENATIK STT Adisutjipto, 2016)
AISI 316L stainless steel is one of the metals that are widely used to meet medical needs. In its use of these materials must meet several requirements such is violence, corrosion resistance, wear resistance and tenacious. To meet these requirements, the modification techniques continue to be developed, such techniques include electropolishing techniques and cold deformation. This research will be carried out merging technique electropolishing and cold deformation which might be expected to obtain the quality 316L stainless steel is better. Research carried out by deform the specimen with a thick reduction of 40% and then do electropolishing process, then performed the test roughness and hardness on the surface of the specimen. Cold deformation 40% increase surface hardness up 105%  from the initial violence. Electropolishing can reduce the surface roughness of up to 14 times.